A Risk Signature With Inflammatory and T Immune Cells Infiltration in Colorectal Cancer Predicting Distant Metastases and Efficiency of Chemotherapy - Hu, Xiang; Li, Ya-Qi; Ma, Xiao-ji; Zhang, Long; Cai, San-Jun; Peng, Jun-Jie (Frontiers in Oncology, 2019)
In order to accurately predict oncological outcomes of colorectal cancer (CRC), we established a risk signature with tumor infiltrating neutrophils and T immune cells for prognosis. A total of 276 CRC patients from FUSCC, and 434 patients from TCGA cohort were enrolled in the study. A risk signature model in combination with CEACAM8+ neutrophils, CD3+, CD8+ T lymphocytes, and FOXP3+ regulatory T cells was established, and the relationships with patient clinicopathological characteristics and prognosis were evaluated. In TCGA cohort, high CEACAM8 expression was observed as an independent factor of poor disease-free survival (DFS), as well as inversely correlated with CD8 (P = 0.0035) and FOXP3 expression (P = 0.05). In the FUSCC cohort for validation, the association between CEACAM8+ neutrophils and DFS had been confirmed in CRC tissue (P = 0.026). Furthermore, a risk stratification was derived from integration of CEACAM8+ neutrophils and T immune cells. In both OS and DFS, the high-risk group all demonstrated worse prognosis than low-risk group, with statistical significance (all P < 0.001). In addition, the high-risk group was correlated with post-operative relapses with accurate prediction. Furthermore, the high-risk group identified a subgroup of CRC patients who appeared not to benefit from adjuvant chemotherapy. At last, predictive nomograms were constructed with recognized independent prognosticators, showing this risk signature increasing the predictive accuracy and efficiency for OS and DFS. In conclusion, incorporation of neutrophil into T lymphocytes could provide more accurate prognostic information in CRC, and this risk stratification predicted for survival benefit from post-operative chemotherapy.